Niche and interspecific association with respect to the dominant phytoplankton species in different hydrological periods of Lake Wuchang, China - Meng, Zihao; Chen, Kang; Liu, Lu; Hu, Feifei; Zhu, Yongjiu; Li, Xuemei; Yang, Deguo (Frontiers in Environmental Science, 2022)
In aquatic ecosystems, the dynamics of ecological parameters play an important role in community organization. To understand the seasonal variation of phytoplankton community in Lake Wuchang, Anhui Province, water samples were collected in three different hydrological periods (Dry season, Normal season, and Wet season) from December 2019 to August 2020. Dominance value (Y), niche width (Bi), niche overlap (Oij), variance ratio method (VR), chi-square test (χ2), and association coefficient were used to analyze the niche and interspecific association with respect to the dominant phytoplankton species in different hydrological periods, while Redundancy analysis method (RDA) was used to distinguish the key driving environmental factors for phytoplankton dominant species. The results showed that 308 species belong to 8 phyla were identified, of which 13 species from 4 phyla were dominant species. From the dry season to wet season, the dominant species changed from Bacillariophyta to Cyanophyta, while Synedra acus was the dominant species throughout the hydrological periods. The niche width of the dominant species varied from 1.77 to 6.65, and the niche width of Dinobryon was smallest while Synedra acus was highest. Niche overlap showed temporal and spatial differences, of which 30 dominant species pairs were greater than 0.600, indicating that they occupied the environmental resources in a high similarity way. The interspecific association results showed that there was a significant positive correlation between the dominant species and genera, especially in normal and wet seasons. Only 10 of 48 dominant species pairs had significant associations based on the χ2 test and two pairs had negative associations in the wet season, which might be related to the hydrological condition in wet season. According to RDA, NO3--N, NH4+-N, PO43--P, water depth (WD), and water temperature (WT) were the key environmental factors affecting the phytoplankton community variation in Wuchang Lake. This paper provides a new perspective for the study of the early warnings regarding cyanobacteria bloom outbreak and the management and protection of water ecological environment in the shallow lakes in the middle-lower reaches of the Yangtze River.